Improving The Competitiveness of Vocational School Students Through Time Management and Productivity Education : Peningkatan Daya Saing Siswa SMK Melalui Edukasi Manajemen Waktu Dan Produktivitas - Yelma Dianastiti; Rico Andhika Putra (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
This community service program aimed to improve the competitiveness of vocational school students through time management and productivity education. The activity was motivated by students’ lack of awareness and skills in organizing their learning and practical schedules effectively. SMKN 2 Tulungagung was chosen as the partner school, considering the high workload and the need for self-discipline among its students. The activity was carried out in the form of a two-hour interactive seminar involving 80 students from various expertise programs. The implementation used lecture, discussion, quiz, and reflection methods to provide direct experience in applying time management techniques such as the Pomodoro Technique, Eisenhower Matrix, and Time Blocking. The results showed a significant increase in students’ awareness and understanding of the importance of time management for academic success and work readiness. About 90% of participants understood how to prioritize tasks effectively, and 85% were motivated to apply the techniques in daily activities. Teachers also responded positively and planned to integrate time discipline values into learning. The post-activity impact indicated the formation of productive habits and a more disciplined learning culture. This program successfully contributed to strengthening students’ soft skills, particularly in discipline, responsibility, and productivity, which are essential to face industrial-era challenges.